2021
DOI: 10.3389/fcell.2020.600575
|View full text |Cite
|
Sign up to set email alerts
|

Microalgae Aurantiochytrium Sp. Increases Neurogenesis and Improves Spatial Learning and Memory in Senescence-Accelerated Mouse-Prone 8 Mice

Abstract: Much attention has recently been focused on nutraceuticals, with minimal adverse effects, developed for preventing or treating neurological diseases such as Alzheimer's disease (AD). The present study was conducted to investigate the potential effect on neural development and function of the microalgae Aurantiochytrium sp. as a nutraceutical. To test neuroprotection by the ethanol extract of Aurantiochytrium (EEA) and a derivative, the n-Hexane layer of EEA (HEEA), amyloid-β-stimulated SH-SY5Y cells, was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 58 publications
5
12
0
Order By: Relevance
“…A neuropeptide NPS increases the excitatory transmitter glutamate secretion and produces anxiolytic-like effects by reducing fear responses [ 49 ]. All these findings align with our previous studies on EEA-SQ that reported antidepressant-like, neuroprotective, and cognition-enhancing effects of EEA-SQ in vivo [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…A neuropeptide NPS increases the excitatory transmitter glutamate secretion and produces anxiolytic-like effects by reducing fear responses [ 49 ]. All these findings align with our previous studies on EEA-SQ that reported antidepressant-like, neuroprotective, and cognition-enhancing effects of EEA-SQ in vivo [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…The EEA-SQ liquid fraction was concentrated using a SpeedVac (Thermo Fisher Scientific, Japan) and then dissolved in Eagle’s minimum essential serum-free medium through sonication (OPTI-MEM; Gibco, Japan). hAECs were treated with EEA-SQ at a 20 µg/mL concentration following our previous studies [ 31 , 32 ] in human neuroblastoma cells (SHSY5Y cells) and neurospheres of mouse neural progenitor cells. EEA-SQ is safe to use on human cells in general.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We observed a significant increase in BrdU+ cell numbers in GSE-administered SAMP8 mice. When we prepared the BrdU in water, 1% sucrose was added to induce drinking similar to our previous publications and we consistently observe similar numbers of BrdU+ cells within groups suggesting that drinking behavior and therefore BrdU dose was not altered [ 33 , 48 , 49 ]. It is also formally possible that GSE increased drinking of water, leading to more BrdU+ cells, however there is no a priori reason to believe this was the case.…”
Section: Discussionmentioning
confidence: 56%